A peptide nucleic acid-functionalized carbon nitride nanosheet as a probe for in situ monitoring of intracellular microRNA1. Issue 12 (21st June 2015) - Liao, Xianjiu; Wang, Quanbo; Ju, Huangxian
<x xml:space="preserve">Abstract</x> In situ intracellular detection of miRNA with an f-CNNS probe.